Analisis Usaha dan Nilai Tambah Kerupuk Gurita di Kecamatan Maje Kabupaten Kaur - Sari, Serlinda Purnama; Mulyasari, Gita; Cahyadinata, Indra; Utama, Satria Putra; Windirah, Nola (Universitas Galuh, 2025)
The octopus cracker business of the Ke'ite Maju Fish Processing and Marketing Group is one of the businesses originating from Maje District, Kaur Regency, where the activities carried out are changing the primary form into new products. The purpose of this study is to analyze the efficiency of the octopus cracker business and analyze the added value of the octopus cracker business of the Ke'ite Maju Fish Processing and Marketing Group in Maje District, Kaur Regency. The research was conducted from October to November 2023. The location determination was carried out deliberately (purposive sampling). The method of determining and taking respondents was carried out deliberately (purposive sampling). To analyze the efficiency of the octopus cracker business, the Ke'ite Maju Fish Processing and Marketing Group in Maje District, Kaur Regency used the Revenue Cost Ratio (R/C Ratio) and Break Even Point (BEP). Meanwhile, to analyze the added value of the octopus cracker business, the Ke'ite Maju Fish Processing and Marketing Group in Maje District, Kaur Regency used the Hayami method. The results of the octopus cracker business analysis have a Revenue Cost Ratio (R/C Ratio) value of 1.42. Break Even Point (BEP) Production of 12 packs and Break Even Point (BEP) Price of Rp. 19,504.34/pack which shows that the octopus cracker business of the Ke'ite Maju Fish Processing and Marketing Group is Efficient to be worked on. Furthermore, the added value of octopus crackers is Rp. 100,358.09/kg with an added value ratio of 61.27 percent. This means that the added value is relatively high.